Brownian alternator - Rattinacannou, J. (D.Ghitu Institute of Electronic Engineering and Nanotechnologies, 2019)
The two-resonator device and the pillar-array version thereof described in a previous manuscript are the subject of a more precise study. The physical interpretation of the device operation is changed for a more appropriate one. The hypothesis on which the pillar-array version is based is revisited and clearly formulated. The pillar-array device is considered under the aspect of an electric generator. This study leads to a new design for this generator. Another resonator is added in order to increase vibrations. The feasibility of an experimental device is addressed. Instructions for the fabrication of a prototype are given.